Dissipation and persistence of thiacloprid in pepper fruits - Lazić, Sanja; Šunjka, Dragana B; Begović, Radovan; Vuković, Slavica M (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
This study gives insight into the behavior of the neonicotinoid insecticide thiacloprid in greenhouse production of pepper. Thiacloprid was applied at a concentration of 96 g a.i./ha, as recommended by the manufacturer for aphid control. Degradation of thiacloprid in pepper fruits was evaluated over a ten-day period, starting from the moment of insecticide application. Sample preparation was performed using the QuEChERS method for liquid chromatography with diode array detection for identification and quantification of thiacloprid residues in extracts of pepper samples. The method was validated in accordance with the SANCO/12571/2013 document. The obtained mean recovery value was 83.69%, with RSD 5.05%. Intraday precision was 3.21%. Within a concentration range from 0.01-2.0 μg/ml, thiacloprid showed linear calibration with R2 0.997%, while the quantification limit of the method was 0.01 mg/kg. The results of a field trial showed that thiacloprid dissipated rapidly from 1.136 mg/kg to 0.321 mg/kg with a loss of 72% in the first two days after application. Throughout the experimental period, thiacloprid residues in pepper fruits basically remained at a stable low level, and no residue exceeding 0.198 mg/kg was detected in the terminal residue experiment, which was below the MRL of 1.0 mg/kg. The half-life (DT50) of thiacloprid in pepper fruits obtained in this study was 4.95 days. Finally, the pre-harvest interval (PHI) for thiacloprid prescribed by Serbian authorities was proved to be safe enough in greenhouse production of pepper.